Integrated Umrah Management Application System (SISKOPATUH) Audit at PT Inayah Haromain Tours & Travel Cilegon - Auliana, Sigit; Permana, Basuki Rakhim Setya; Aryono, Gagah Dwiki Putra; Andriani, Fipi (ARRUS Journal of Engineering and Technology, 2024)
In organizing Umrah worship trips, there is a monitoring system launched by the Ministry of Religion in August 2019, namely the Umrah Integrated Management Computerization System. The purpose of this study is to determine the application of audits on the SISKOPATUH Application to evaluate and make the results as input to improve the management of this application at PT Inayah Haromain Tours & Travel. In the procedure for conducting an audit of this application carried out by researchers, it includes a process, namely: preliminary examination, further examination, examination results, discussion of examination results and recommendations / proposals, then an examination report. The results showed that there were problems that occurred in this Information System, namely the existence of a timer in the data entry system which caused the data to become more than one if the data input was long. The application of the SISKOPATUH Application Information System at PT Inayah Haromain Tours & Travel is still not efficient because there are still many resources that have not mastered this application, as well as the lack of government concern to socialize to technical personnel so that nothing detrimental to both parties occurs.